2020
DOI: 10.1017/nps.2020.9
|View full text |Cite
|
Sign up to set email alerts
|

Nationalism and Sport: A Review of the Field

Abstract: The connection between nationalism and sport seems at once both obvious and manifest, with the most lavish praise of the nation often arising at sporting events. While a sizeable body of academic literature exists on the connection between the two concepts, it remains overlapping and unstructured. This state of the field review essay accounts for the major works in this field and categorizes it according to the function it fulfills in the subfield. Specifically, it focuses on sport as a mechanism for the diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 44 publications
0
6
0
1
Order By: Relevance
“…As many studies have shown, nation image, gender identity, and the body, and other elements are intertwined with ideologies like globalization and modernization on the stage of the Olympic Games (Arnold, 2021;de Haan et al, 2015;Jones et al, 2016). Hosting the Olympic Games is an excellent opportunity to shape a brand and showcase culture and image in contemporary global geopolitics.…”
Section: Discussionmentioning
confidence: 99%
“…As many studies have shown, nation image, gender identity, and the body, and other elements are intertwined with ideologies like globalization and modernization on the stage of the Olympic Games (Arnold, 2021;de Haan et al, 2015;Jones et al, 2016). Hosting the Olympic Games is an excellent opportunity to shape a brand and showcase culture and image in contemporary global geopolitics.…”
Section: Discussionmentioning
confidence: 99%
“…3) Nationalism: Nationalism showcases how individual and collective factors generate identities together in a world no longer animated by corporate identities [39] [40]. Sport has been acknowledged as the vehicle in defining national identities, generating belonging and promoting nationalism under globalization [41] [42].…”
Section: The Theory Of Framing In This Researchmentioning
confidence: 99%
“…It is difficult to deny the persisting political implications of this football rivalry, and the different articulations of "nationalism" (Arnold, 2021) brought to the fore each time the two teams play each other. At the same time, the high mediatisation of the event, and its global profile as the best testimonial for La Liga and Spanish football, has magnified sensationalistic journalistic practices which complicate and confuse the cultural boundaries of the historical rivalry (Ginesta et al, 2020).…”
Section: Football and Contested Identitiesmentioning
confidence: 99%